The response of the different soybean metallothionein isoforms to cadmium intoxication - Pagani, María Ayelén (2012)
Cadmium is a highly toxic heavy metal for both plants and animals. The presence of Cd in agricultural soils is of major concern regarding its entry into the food chain, since Cd compounds are readily taken up by plants, and accumulated in edible parts due to their high solubility. In this study, we first demonstrate the high capacity for Cd concentration of soybean grains. Consequently, we considered the study and characterization of the molecular determinants of Cd accumulation -such as metallothioneins (MT)- to be of major practical importance. We report here the first characterization of the soybean MT system, with the identification of nine genes (one of which is a truncated pseudogene), belonging to the four plant MT types. The most highly expressed of each type was chosen for further function analysis. All of them are expressed at high levels in soybean tissues: GmMT1, GmMT2 and GmMT3 in roots, shoots and seeds, and GmMT4 only in seeds. The corresponding recombinant soybean MTs, synthesized in Escherichia coli cells cultured in metal supplemented media, exhibit greater cadmium than zinc binding capacity. These results suggest a definite role of GmMTs in Cd(II) accumulation as one of the main responses of soybean to an overload of this metal.